Left atrial volume and cardiovascular outcomes in systolic heart failure: effect of antithrombotic treatment. (17th July 2018) - Di Tullio, Marco R.; Qian, Min; Thompson, John L.P.; Labovitz, Arthur J.; Mann, Douglas L.; Sacco, Ralph L.; Pullicino, Patrick M.; Freudenberger, Ronald S.; Teerlink, John R.; Graham, Susan; Lip, Gregory Y.H.; Levin, Bruce; et al.
Abstract: Aims: Left atrium (LA) dilation is associated with adverse cardiovascular (CV) outcomes. Blood stasis, thrombus formation and atrial fibrillation may occur, especially in heart failure (HF) patients. It is not known whether preventive antithrombotic treatment may decrease the incidence of CV events in HF patients with LA enlargement. We investigated the relationship between LA enlargement and CV outcomes in HF patients and the effect of different antithrombotic treatments. Methods and results: Two‐dimensional echocardiography with LA volume index (LAVi) measurement was performed in 1148 patients with systolic HF from the Warfarin versus Aspirin in Reduced Ejection Fraction (WARCEF) trial. Patients were randomized to warfarin or aspirin and followed for 3.4 ± 1.7 years. While the primary aim of the trial was a composite of ischaemic stroke, death, and intracerebral haemorrhage, the present report focuses on the individual CV events, whose incidence was compared across different LAVi and treatment subgroups. After adjustment for demographics and clinical covariates, moderate or severe LA enlargement was significantly associated with total death (hazard ratio 1.6 and 2.7, respectively), CV death (HR 1.7 and 3.3), and HF hospitalization (HR 2.3 and 2.6) but not myocardial infarction (HR 1.0 and 1.4) or ischaemic stroke (1.1 and 1.5). The increased risk was observed in both patients treated with warfarin or aspirin. In warfarin‐treated patients, a time in therapeutic range >60% was associated with lower event rates, and an interaction between LAVi and time in therapeutic range was observed for death ( P = 0.034). Conclusions: In patients with systolic HF, moderate or severe LA enlargement is associated with death and HF hospitalization despite treatment with antithrombotic medications. The possibility that achieving a more consistent therapeutic level of anticoagulation may decrease the risk of death requires further investigation.